Analysis Oflogic Fuzzy On Fuzzy Logic Controller (FLC) For Nutrient Film Technique (NFT) - Siahaan J; Cucus A (International Conference on Engineering and Technology Development (ICETD), 2017)
Intriduction1.1BackgroundIn the middle of the technological developments that have led many science and innovation, in terms of providing ease of field work. It also influenced the development in one field of agriculture, makingit more efficient and effective. One such development is the automatic control system in which there are a method (knowledge base) that is able to give a decision in the control system in hydroponiccultivation. Hydroponics can be interpreted as a construction or management of water as a medium to grow plants without using soil as a growing medium media and take the required mineral nutrientsfrom the nutrient solution dissolved in water (Istiqomah, 2007). Where in general the field of agriculture requires the availability of a large area, so that a barrier in urban areas with limited arableland available. Hydroponic cultivation system into a system that is very helpful in terms of a narrow land use (Musyarofah, 2010). One of the hydroponic system is the method of Nutrient FilmTechnique(NFT) is the method of cultivation in which the plant roots grow in the shallow water layer and circulate allowing the plants get water, nutrients and oxygen